Programa De Atención E Intervención Psicosocial Orientado A La Rehabilitación Psicosocial De La Violencia Intrafamiliar En Cuatro Familias Vinculadas Al Banco De Alimentos Del Municipio De Cajicá - Cardoso Forero, Cristian Camilo (Universidad Antonio Nariño, 2023)
Domestic violence against children and adolescents is defined as the acts or negligence carried out by parents, relatives or guardians, which can cause pain or physical, psychological and / or sexual harm to the victim (Ribero, Sánchez. 2004)